PARADE IKLAN POLITIK DI TAHUN POLITIK: Polarisasi Penggunaan Iklan Untuk Membangun Citra Menuju Pemilu 2014 - Firdaus, Firdaus (Turast: Jurnal Penelitian dan Pengabdian, 2013)
2013-2014 is known as the political years. The program to power transition—general election—will be heldin these years. For various political parties and politicians, the period is used to promote their political image.Advertisement is a choice essentially used to build their political branding. Political Advertisement is functionedto influence the constituent—to vote the political parties or politicians. The research concerns to certaintlyexamine the pattern of polarization of political campaign—advertisement—to build a political image in 2014.